2021
DOI: 10.1007/s11356-021-17783-x
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of microbes and prediction of their functions in karst caves under the influence of human tourism activities—a case study of Zhijin Cave in Southwest China

Abstract: Microorganisms, sensitive to the surrounding environment changes, show how the cave environment can be impacted by human activities. Zhijin Cave, featured with the most well-developed karst landform in China, has been open to tourists for more than 30 years. This study explored the microbial diversity in a karst cave and the impacts of tourism activities on the microbial communities and the community structures of bacteria and archaea in three niches in Zhijin Cave, including the mixture of bacteria and cyanob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
4
5
0
Order By: Relevance
“…The proteins related to ATP binding, such as iron (III) transport system ATP-binding protein [EC: 3.6.3.30], branched-chain amino acid transport system ATP-binding protein, and putative spermidine/putrescine transport system ATP-binding protein, were dominant in DW samples (Figure 5C). Overall, Thaumarchaeota and Crenarchaeota were reported to be dominant in karst niches, such as weathered rocks, sediments within the cave and soils outside the cave (Ai et al, 2022), which were consistent with our results mainly dominated by Thaumarchaeota, with a relative abundance ranging from 0.23 ± 0.14% to 21.69 ± 8.88% (Figure 1D; Supplementary Table 2). Thaumarchaeota might associate with the acidic environment due to their dominance in the acidic cave with a pH value ranging from 4.97 to 6.88 (Barton et al, 2014).…”
Section: Microbial Functional Inference and Ecological Trait Assignme...supporting
confidence: 90%
See 1 more Smart Citation
“…The proteins related to ATP binding, such as iron (III) transport system ATP-binding protein [EC: 3.6.3.30], branched-chain amino acid transport system ATP-binding protein, and putative spermidine/putrescine transport system ATP-binding protein, were dominant in DW samples (Figure 5C). Overall, Thaumarchaeota and Crenarchaeota were reported to be dominant in karst niches, such as weathered rocks, sediments within the cave and soils outside the cave (Ai et al, 2022), which were consistent with our results mainly dominated by Thaumarchaeota, with a relative abundance ranging from 0.23 ± 0.14% to 21.69 ± 8.88% (Figure 1D; Supplementary Table 2). Thaumarchaeota might associate with the acidic environment due to their dominance in the acidic cave with a pH value ranging from 4.97 to 6.88 (Barton et al, 2014).…”
Section: Microbial Functional Inference and Ecological Trait Assignme...supporting
confidence: 90%
“…The sediments in the dark zone of the Heshang Cave were covered with bat guano, the dominance of Euryarchaeota in our cave was consistent with previous studies. Simultaneously, high Shannon indices of archaea and bacteria were observed in the Heshang Cave ecosystem (Figures 1A,B) compared with the previous reports (Ai et al, 2022;Xiao et al, 2022). SD was dominant by Rokubacteria (24.22 ± 5.99%) and GAL15 (13.03 ± 4.29%) (Figure 1D, Supplementary Table 2).…”
Section: Microbial Functional Inference and Ecological Trait Assignme...supporting
confidence: 64%
“…The exquisite frescoes are located in the back room of the Qinling Mausoleum, which attracted larger numbers of visitors to the back room due to interest in the frescoes. The difference may have been caused by the tourist activity [13,44,45]. Therefore, it can be assumed that the tourism-related activity could have promoted the shifts in the microbial community diversity in the back room of the Qinling Mausoleum.…”
Section: Tourism-related Activity Drives Microbial Community Shiftmentioning
confidence: 99%
“…In this study, a significant increase of Cyanobacteria was found in the back room of the Qinling Mausoleum. It should be noted that the colonized Cyanobacteria could cause aesthetic, physical and chemical damages to historical relics [19,44,51]. Fourthly, inspiration from numerous visitors has raised the CO 2 concentration levels inside the tomb [44,54], intensifying the corrosion of the walls and facilitating microbial proliferation that could accelerate biodeterioration [49,55].…”
Section: Tourism-related Activity Drives Microbial Community Shiftmentioning
confidence: 99%
See 1 more Smart Citation